Complete chloroplast genomes of two Miscanthus species. (1st November 2016) - Nah, Gyoungju; Im, Ji-Hoon; Lim, Soo-Hyun; Kim, Kyunghee; Choi, Ah Young; Yook, Min Jung; Kim, Soonok; Kim, Changmu; Kim, Do-Soon
Abstract: The complete chloroplast (cp) genomes of two Miscanthus species, M. sinensis and M. sacchariflorus, were sequenced and investigated for genes, genome size variation, and polymorphisms. There are 170 genes in both cp genomes, consisting of 122 mRNA genes (84 protein-coding genes and 38 hypothetical genes), 40 tRNA genes, and 8 rRNA genes. The cp genome contains two inverted repeat (IR) regions, separated by large single copy (LSC) region and small single copy (SSC) region. Indels were responsible for 40 bp difference in cp genome size in two species. In addition, we established phylogenetic relationship with other monocot cp genomes, and estimated divergence time. The two Miscanthus species clustered together among other C4 monocot species and the divergence time of two Miscanthus species was approximately 0.5 1–0.84 Mya.